MntC-Dependent Manganese Transport Is Essential for Staphylococcus aureus Oxidative Stress Resistance and Virulence - Luke D. Handke (American Society for Microbiology, 2018)
ABSTRACT Staphylococcus aureus is a human pathogen that has developed several approaches to evade the immune system, including a strategy to resist oxidative killing by phagocytes. This resistance is mediated by production of superoxide dismutase (SOD) enzymes which use manganese as a cofactor. S. aureus encodes two manganese ion transporters, MntABC and MntH, and a possible Nramp family manganese transporter, exemplified by S. aureus N315 SA1432. Their relative contributions to manganese transport have not been well defined in clinically relevant isolates. For this purpose, insertional inactivation mutations were introduced into mntC, mntH, and SA1432 individually and in combination. mntC was necessary for full resistance to methyl viologen, a compound that generates intracellular free radicals. In contrast, strains with an intact mntH gene had a minimal increase in resistance that was revealed only in mntC strains, and no change was observed upon mutation of SA1432 in strains lacking both mntC and mntH. Similarly, MntC alone was required for high cellular SOD activity. In addition, mntC strains were attenuated in a murine sepsis model. To further link these observations to manganese transport, an S. aureus MntC protein lacking manganese binding activity was designed, expressed, and purified. While circular dichroism experiments demonstrated that the secondary and tertiary structures of this protein were unaltered, a defect in manganese binding was confirmed by isothermal titration calorimetry. Unlike complementation with wild-type mntC, introduction of the manganese-binding defective allele into the chromosome of an mntC strain did not restore resistance to oxidative stress or virulence. Collectively, these results underscore the importance of MntC-dependent manganese transport in S. aureus oxidative stress resistance and virulence. IMPORTANCE Work outlined in this report demonstrated that MntC-dependent manganese transport is required for S. aureus virulence. These study results support the model that MntC-specific antibodies elicited by a vaccine have the potential to disrupt S. aureus manganese transport and thus abrogate to its virulence.